2019
DOI: 10.1002/ange.201813305
|View full text |Cite
|
Sign up to set email alerts
|

Interconverting Lanthanum Hydride and Borohydride Catalysts for C=O Reduction and C−O Bond Cleavage

Abstract: The high catalytic reactivity of homoleptic tris(alkyl) lanthanum La{C(SiHMe 2 ) 3 } 3 is highlighted by C À Ob ond cleavage in the hydroboration of esters and epoxides at room temperature.T he catalytic hydroboration tolerates functionality typically susceptible to insertion, reduction, or cleavage reactions.T urnover numbers (TON) up to 10 000 are observed for aliphatic esters.L anthanum hydrides,g enerated by reactions with pinacolborane,a re competent for reduction of ketones but are inert toward esters.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Both materials 1@MSN550 and 1@MSN700 proved to be effective precatalysts at 5 mol % La loading (relative to epoxide) for ring opening C-O bond cleavage of epoxides via hydroboration to give borate esters, and both performed similarly in terms of activity and product yield ( Table 4). These reaction performance metrics are comparable, and often superior, to the soluble catalyst precursor La{C(SiHMe2)3}3; 12 in several cases the supported catalyst out-performed the homogeneous precursor. These organolanthanide catalysts also are advantaged over the state-of-the art transition-metalbased catalysts, which are limited to conversions of styrenyl oxides.…”
Section: Catalytic Hydroboration Of Epoxides With Hbpin Using 1@msnmentioning
confidence: 85%
See 3 more Smart Citations
“…Both materials 1@MSN550 and 1@MSN700 proved to be effective precatalysts at 5 mol % La loading (relative to epoxide) for ring opening C-O bond cleavage of epoxides via hydroboration to give borate esters, and both performed similarly in terms of activity and product yield ( Table 4). These reaction performance metrics are comparable, and often superior, to the soluble catalyst precursor La{C(SiHMe2)3}3; 12 in several cases the supported catalyst out-performed the homogeneous precursor. These organolanthanide catalysts also are advantaged over the state-of-the art transition-metalbased catalysts, which are limited to conversions of styrenyl oxides.…”
Section: Catalytic Hydroboration Of Epoxides With Hbpin Using 1@msnmentioning
confidence: 85%
“…In addition, the supported organolanthanide also provided improved selectivity in the catalytic ring-opening hydroboration of cis-stilbene oxide, giving 1,2diphenylethanol, whereas the soluble catalyst precursor La{C(SiHMe2)3}3 afforded a mixture of 1,2-diphenylethanol and a rearranged 2,2-diphenylethanol product. 12 The catalytic activity of 1@MSN was solely associated with the solid material, even though soluble 1 is a viable catalyst in its own right. Styrene oxide ring-opening hydroboration reactions, in which half of the supernatant solution was separated from the reaction mixture and filtered after 1 h (at ca.…”
Section: Catalytic Hydroboration Of Epoxides With Hbpin Using 1@msnmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Nembenna's group disclosed that magnesium amide complexes could be served as highly efficient catalysts for hydroboration of a broad range of esters with pinacolborane (HBpin) . Very recently, Sadow and co‐workers further found that the homoleptic tris(alkyl)lanthanum complex La{C(SiHMe 2 ) 3 } 3 was competent to catalyze the hydroboration of esters and epoxides at room temperature . Apart from aforementioned work, the ester is only acted as sole example of substrates that has been sporadically reported …”
Section: Background and Originality Contentmentioning
confidence: 99%